A New Cross-National Measure of Corruption - Escresa, Laarni (Published by Oxford University Press on behalf of the World Bank, 2018)
A new measure of cross-national corruption is constructed based on the geographic distribution of public officials involved in cross-border corruption cases. A comparison is made between the Public Administration Corruption Index (PACI) and perception-based measures, considers the extent to which differences between them are driven by systematic factors, and concludes that they are not. As more data on cases of cross-border bribery incidents become available, the PACI will provide an increasingly valid cross-national measure of corruption.